Strategi Manajemen Keuangan Perusahaan Pariwisata dalam Menghadapi Pandemi Covid-19 - Rizal Diansyah; Ira Geraldina; Julianto Agung Saputro (Syntax Corporation, 2023)
Tourism is one sector that has a major impact on the community's economy. The tourism sector absorbs a lot of labor, increases regional income, and increases the country's foreign exchange. Since the Covid-19 case appeared in Indonesia in March 2020, the tourism sector has experienced a drastic decline in income. This is due to a policy that prohibits mobility between regions and the closure of tourist destinations in red-zone areas. The right financial management strategy is very important because companies must be adaptive and innovative to survive. This study aims to analyze the financial management strategy of Perumda Owabong and BUMDes Serang Makmur Sejahtera in dealing with the Covid-19 pandemic. The method used in this study is a qualitative method with a comparative approach. The informants in this study were top management at Perumda Owabong and BUMDes Serang Makmur Sejahtera. The results of this study indicate that the financial management strategies used by Perumda Owabong and BUMDes Serang Makmur in dealing with the Covid-19 pandemic are broadly the same, namely defensive and diversified management strategies but with their own uniqueness